The impact of internal factors on business success among SMEs in Kuala Lumpur - Aziz, Nur Akmal Syahirah (2019)
The purpose of the research is to identify whether the internal factors such as entrepreneurial competency, marketing capability, financial resources, technology usage, and knowledge sharing were related in business success among SMEs in Kuala Lumpur. The data was collected among 190 respondents from the total SMEs in Kuala Lumpur. Simple random sampling technique and area sampling has been used as a sampling technique. The data collected then key in using SPSS (Statistical Package for Social Science) to analyse all the data gathered through the questionnaire. Several analysis have been done by using the SPSS such as reliability analysis, frequency distribution, descriptive and multiple regression. Based on the data obtained, only one independent variable (financial resources) has positive relationship with the business success of SMEs in Kuala Lumpur.